Accurate tip characterization in critical dimension atomic force microscopy. (30th April 2020) - Dai, Gaoliang; Xu, Linyan; Hahm, Kai
Abstract: A new method for accurately characterizing the tip geometry of critical dimension atomic force microscopy (CD-AFM) has been introduced. A sample type IVPS100-PTB whose line features have vertical sidewall, round corner with a radius of approx. 5 ∼ 6 nm and very low surface roughness has been applied as the tip characterizer. The geometry of the line features has been accurately and traceably calibrated to the lattice constant of crystal silicon. In this paper, detailed measurement strategies and data evaluation algorithms have been introduced, particularly concerning several important influence factors such as the line width roughness of the tip characterizer, measurement noise, measurement point density, and the calculation of the averaged tip geometry. Thorough experimental studies have been carried out, indicating high measurement accuracy of the developed method. For instance, tip geometry of a probe type CDR120 with a nominal tip diameter of 120 nm is reconstructed using two different tip characterizers before, during and after it is applied for a calibration of a user sample. The agreement of all 20 obtained tip profiles reaches 0.4 nm, confirming the high measurement stability, low tip wear as well as the high measurement consistency between two tip characterizers. Furthermore, the results of a nanofeature of the user sample after correcting the tip contribution show a repeatability of approximately 0.3 nm when it is repeatedly measured by a same tip, and a reproducibility of 0.9 nm when it is measured using two different tips, confirming the good performance of the tip correction method as well.